'Weak ally' or 'strong enemy?': Japan in the eyes of Russian diplomats and military agents, 1900-1907. Issue 3 (2nd July 2016) - Podalko, Petr E.
Abstract: At the dawn of the twentieth century, ignorance towards the growing military power of Japan led Imperial Russia to her unexpected and decisive loss of the war of 1904–1905. Just ten years earlier in 1895, Japan was almost half-robbed of the spoils of her victory over China by the Western Powers (including Russia), which insisted on revising the Treaty of Shimonoseki. The Boxer Rebellion of 1899–1901 stopped this confrontation and turned Japan and Russia into allies for a short time: Russian and Japanese soldiers fought together against the Chinese, constituting the two largest units among the five allied troops with Russians playing the leading role on the battlefield and the Japanese being their loyal deputy (as it was viewed by Russian media of the time). All these circumstances led Russia to underestimate the Japanese army in the following years. However, the Russo-Japanese War itself changed that attitude, turning it into a sort of 'a-next-war-to-be-hysteria' among the Russian officials who served in Japan after the war. The reports by Russian military agents and diplomats from special collections in the Hoover Institution of War, Columbia University, and other archives used in this paper show us that despite being their government's only 'eyes' watching the Orient, sometimes those eyes were 'blinded' by the loss in the recent war and by their own experiences. One major reason for this was that many Russian diplomats, military agents and spies had long been serving in the Far East, and for some of them the transformation of Japan from 'weak ally' to 'strong enemy' status happened so swiftly, they came to overestimate this new 'peril.' Another problem was Japanese language skill. In the same way that Russia could not properly predict the growing power of Japan before 1904, she wanted after the war to obtain all possible information about her neighbor and, thus, paid special attention to educating a new generation of oriental specialists.